Evaluation of Religious Tolerance Education in Developing Inclusive Attitudes of Multireligious Elementary School Students - Mega Selvi Maharani; Rafika Oktapiyani (GHAITSA : Islamic Education Journal, 2026)
Religious tolerance is the attitude of respecting and honoring people who have different religions, cultures, or races. Indonesia has six recognized religions, which means that it is important for Indonesian citizens to encourage and practice a tolerant attitude since an early age. This research aims to evaluate religious tolerance education in developing inclusive attitudes among students at the multi-religious elementary school. The subjects of the research are the Principal, Vise Principal, Class Teachers, Class Students, PAI Teachers, and Buddhist Religion Teachers of state elementary school 04 Uajan Mas. This research is an evaluation study using the Goal Oriented Evaluation model by using a qualitative approach. The research results indicate that there are two school's objectives include general objectives, such as cultivating students’ faithful, pious, and of noble character, and specific objectives such integrating tolerance values. The organization of learning experiences is accomplished through the rule of the school, teachers, and students, using strategies such as learning integration, habituation, religious activities, teacher exemplification, and the cultivation of attitudes and character among students. The results of the learning experiences demonstrate an increase in mutual respect, deliberation skills, self-awareness, and the practice of tolerance, although there is a tendency for a few students to associate with groups of people based on their religion. The implications of this research could function as a framework for schools to design subsequent initiatives to strengthen tolerance education, such as the development of a multicultural-based curriculum, teacher training, and the provision of an inclusive school environment